2012
DOI: 10.1016/j.jecp.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term transfer of learning from books and video during toddlerhood

Abstract: Television viewing and picture book reading are prevalent activities during toddlerhood and research has shown that toddlers can imitate from both books and videos after short delays (Barr & Hayne, 1999; Simcock & DeLoache, 2006). This is the first study to directly compare toddlers’ long-term retention rates for target actions learned from a video or book. Toddlers (N = 158) aged 18- and 24-months saw an experimenter demonstrating how to make a novel 3-step toy rattle via a pre-recorded video or a picture boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 51 publications
1
32
0
1
Order By: Relevance
“…An initial examination of the mean baseline imitation scores showed a different pattern of results for the 2D test ( M = 0.21) and 3D test ( M = 0.04) conditions. Therefore, we created difference scores to equate for the higher mean in the 2D test baseline group (cf., Brito, Barr, McIntyre & Simcock, 2011 for a similar approach). A difference score was calculated for each participant by subtracting the mean of the corresponding test dimension baseline from each participant’s imitation score.…”
Section: Resultsmentioning
confidence: 99%
“…An initial examination of the mean baseline imitation scores showed a different pattern of results for the 2D test ( M = 0.21) and 3D test ( M = 0.04) conditions. Therefore, we created difference scores to equate for the higher mean in the 2D test baseline group (cf., Brito, Barr, McIntyre & Simcock, 2011 for a similar approach). A difference score was calculated for each participant by subtracting the mean of the corresponding test dimension baseline from each participant’s imitation score.…”
Section: Resultsmentioning
confidence: 99%
“…Factors such as the type of information to be transferred, how learning is measured (goals or gestures), the amount of exposure prior to test, and the delay duration are all likely to play a role in children's success at transferring information across dimensional changes. Further studies with both adults and children are needed to assess the contribution of these factors (see also Brito, Barr, McIntyre, & Simcock, ; Klahr & Chen, ; Triona & Klahr, ; Zack, Barr, Gerhardstein, Dickerson, & Meltzoff, ).…”
Section: Discussionmentioning
confidence: 99%
“…21 The few experimental studies showing independent learning of words from videos at this age have been limited by their low ecologic validity 22 or have shown that toddlers lose the knowledge learned over time without repetition. 23 More recent research has shown that, under particular conditions, children between 15 and 24 months of age can learn from repeated viewing of video demonstrations without adult help. Dayanim and Namy showed that 15-month-olds could learn the meaning of sign language symbols after 3 weeks of watching a commercially available video 4 times per week.…”
Section: At What Age Can Infants and Toddlers Learn From Screens?mentioning
confidence: 99%